Re-envisioning Libraries: Process and Best Practices - Moyo, Lesley (My University, 2016)
Presentation content: The need for library transformation; Engaging stakeholders in the development of a strategic framework; Applying the framework to develop and implement a change agenda: Rethinking service delivery model; Library consolidation; Facilities master planning
Keywords: Library connect; library seminar; library transformation